CO oxidation catalyzed by the single Co atom embedded hexagonal boron nitride nanosheet: a DFT-D study. Issue 31 (20th July 2016) - Lu, Zhansheng; Lv, Peng; Liang, Yanli; Ma, Dongwei; Zhang, Yi; Zhang, Wenjin; Yang, Xinwei; Yang, Zongxian
Abstract : A single metal atom stabilized on two dimensional materials (such as graphene and h-BN) exhibits extraordinary activity in the oxidation of CO. Abstract : A single metal atom stabilized on two dimensional materials (such as graphene and h-BN) exhibits extraordinary activity in the oxidation of CO. The oxidation of CO by molecular O2 on a single cobalt atom embedded in a hexagonal boron nitride monolayer (h-BN) is investigated using first-principles calculations with dispersion-correction. It is found that the single Co atom prefers to reside in a boron vacancy and possesses great stability. There are three mechanisms for CO oxidation: the traditional Eley–Rideal (ER) and Langmuir–Hinshelwood (LH) mechanisms and the termolecular Eley–Rideal (TER) mechanism proposed recently. Given the relatively small reaction barriers of the rate-limiting steps for the ER, LH and TER mechanisms (0.59, 0.55 and 0.41 eV, respectively), all three mechanisms are able to occur at low temperature. The current study may provide useful clues to develop low cost single atom catalysts.